2019
DOI: 10.37828/em.2019.22.6
|View full text |Cite
|
Sign up to set email alerts
|

Oribatid Mites (Acari: Oribatida) Phoretic on Passalid Beetles (Coleoptera: Passalidae), With Description of a New Species From Indonesia

Abstract: A new species of oribatid mites (Oribatida) phoretic on the beetle, Macrolinus batesi (Coleoptera, Passalidae) is described from Sumatra, Indonesia. Graptoppia (Stenoppia) royi sp. nov. (Oppiidae) differs from G. (S.) italica by the smaller body size, the presence of thin transcostula and the absence of costulae. Data on oribatids phoretic on passalid beetles are summarized; nine identified oribatid species (from 19 beetle species) are listed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…As previously noted (Norton 1980;Ermilov 2019;Ermilov & Frolov 2019a, b), some oribatid mites are actively phoretic on insects, having morphological adaptations for attachment to the host (for example, gripping setae of beetles between the rostrum of the aspis and the anterior portion of the genital plates in ptyctimous mites, or specifically curved leg claws for holding onto setae of the host as in Siculobata (Paraleius)) (Norton 1980).…”
Section: General Remarksmentioning
confidence: 81%
See 3 more Smart Citations
“…As previously noted (Norton 1980;Ermilov 2019;Ermilov & Frolov 2019a, b), some oribatid mites are actively phoretic on insects, having morphological adaptations for attachment to the host (for example, gripping setae of beetles between the rostrum of the aspis and the anterior portion of the genital plates in ptyctimous mites, or specifically curved leg claws for holding onto setae of the host as in Siculobata (Paraleius)) (Norton 1980).…”
Section: General Remarksmentioning
confidence: 81%
“…Beetles of the family Passalidae are one of the more common insect hosts actively used by oribatid mites for phoresy (Ermilov 2019), however, phoretic oribatid mites had not been previously reported from A. lamellatus, nor from any beetles of the family Zopheridae. Hence, our findings (P. paracuriosus n. sp.…”
Section: General Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Many oribatids can migrate over large distances with the wind (anemohydrochory) [84][85][86][87], via birds [88][89][90][91][92], by water currents or waves (together with the action of wind), or with objects drifting in water [84,86,93], including transport in seawater [94]. Even though Oribatida lack obvious morphological adaptations for active transport by phoresy, it has been demonstrated that they are carried on insects [95][96][97][98][99][100] and frogs [101].…”
Section: Ecology and Distributionmentioning
confidence: 99%